Is habitat fragmentation bad for biodiversity?. (February 2019) - Fahrig, Lenore; Arroyo-Rodríguez, Víctor; Bennett, Joseph R.; Boucher-Lalonde, Véronique; Cazetta, Eliana; Currie, David J.; Eigenbrod, Felix; Ford, Adam T.; Harrison, Susan P.; Jaeger, Jochen A.G.; Koper, Nicola; Martin, Amanda E.; et al.
Abstract: In a review of landscape-scale empirical studies, Fahrig (2017a) found that ecological responses to habitat fragmentation per se (fragmentation independent of habitat amount) were usually non-significant (>70% of responses) and that 76% of significant relationships were positive, with species abundance, occurrence, richness, and other response variables increasing with habitat fragmentation per se. Fahrig concluded that to date there is no empirical evidence supporting the widespread assumption that a group of small habitat patches generally has lower ecological value than large patches of the same total area. Fletcher et al. (2018) dispute this conclusion, arguing that the literature to date indicates generally negative ecological effects of habitat fragmentation per se. They base their argument largely on extrapolation from patch-scale patterns and mechanisms (effects of patch size and isolation, and edge effects) to landscape-scale effects of habitat fragmentation. We argue that such extrapolation is unreliable because: (1) it ignores other mechanisms, especially those acting at landscape scales (e.g., increased habitat diversity, spreading of risk, landscape complementation) that can counteract effects of the documented patch-scale mechanisms; and (2) extrapolation of a small-scale mechanism to a large-scale pattern is not evidence of that pattern but, rather a prediction that must be tested at the larger scale. Such tests were the subject of Fahrig's review. We find no support for Fletcher et al.'s claim that biases in Fahrig's review would alter its conclusions. We encourage further landscape-scale empirical studies of effects of habitat fragmentation per se, and research aimed at uncovering the mechanisms that underlie positive fragmentation effects. Highlights: Habitat fragmentation per se is a landscape-scale phenomenon. Cross-scale extrapolation from edge effects to fragmentation effects is unreliable. Most responses to habitat fragmentation per se are non-significant. Most significant responses to habitat fragmentation per se are positive. Sets of small habitat patches with a large total area have high conservation value.